Short-term international capital flows: empirical evidence from China - Junjun, Tan; Mansor Jusoh,; Tamat Sarmidi, (Penerbit Universiti Kebangsaan Malaysia, 2013)
The present study investigates the dynamic relationship between short-term international capital flows and macroeconomic variables in China from 1999 until 2011. Employing the bounds test, autoregressive distributed lag (ARDL) model and Granger causality tests, the results show that interest rate differentials and real estate prices are the main driving forces for short-term international capital movements. The Granger causality test indicates that interest rate differentials and exchange rates Granger cause the short-term international capital flows of China in the short run; while bidirectional causal relationships are found among short-term international capital flows and interest rate differentials; effective exchange rates; stock prices; and real estate prices in the long run.